2021
DOI: 10.1007/s00107-021-01699-x
|View full text |Cite
|
Sign up to set email alerts
|

High-cycle fatigue behaviour of a timber-to-timber connection with self-tapping screws under lateral loading

Abstract: The high-cycle fatigue behaviour of a timber-to-timber connection with self-tapping screws is examined with the fasteners under bending due to their alignment lateral to the load direction. The cyclic tests were carried out with a sinusoidal non-reversed load ($$R=0.1$$ R = 0.1 ) with a loading frequency of 5 Hz. The examined connection is designed for the quasistatic failure mechanism with two plastic hinges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Lower stress levels led to failure in the fastener itself which has already been examined by Niebuhr and Sieder (2020) for the fastener used here. Beyond that, a distinct influence of the specimen density on the quasistatic capacity and hence on the stress level could be observed (analogous to the findings by Niebuhr and Sieder, 2021), which is why one nominal stress level was found to be sufficient to derive a viable Wöhler-curve for the limited stress-level span 0.75 ≤ S < 1.0. The maximum forces in the cyclic series were determined with the mean ultimate loads from the quasistatic series: F max = S • F ult,mean .…”
Section: Experimental Programmesupporting
confidence: 74%
See 4 more Smart Citations
“…Lower stress levels led to failure in the fastener itself which has already been examined by Niebuhr and Sieder (2020) for the fastener used here. Beyond that, a distinct influence of the specimen density on the quasistatic capacity and hence on the stress level could be observed (analogous to the findings by Niebuhr and Sieder, 2021), which is why one nominal stress level was found to be sufficient to derive a viable Wöhler-curve for the limited stress-level span 0.75 ≤ S < 1.0. The maximum forces in the cyclic series were determined with the mean ultimate loads from the quasistatic series: F max = S • F ult,mean .…”
Section: Experimental Programmesupporting
confidence: 74%
“…As described in Section 3.1 some bending in the fastener has to be assumed due to the inclination of the fastener with regard to the force direction. Niebuhr and Sieder (2021) showed that the performance of the examined fastener is superior if the axial fastener stresses are caused by bending rather than an axial force as is known for other threaded fasteners such as steel bolts (cf., e.g., Agatonovic, 1973;Schaumann and Marten, 2009). Hence, a safe side approximation of the behaviour under bending or combined loading is possible with S-N-curves determined with pure axial loading if the actual fastener stresses with consideration of bending are utilised.…”
Section: Involved Fatigue Phenomenamentioning
confidence: 89%
See 3 more Smart Citations